DOI: 10.14264/uql.2015.396
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gene family evolution and the molecular basis of shell formation in molluscs

Abstract: Since the emergence of shell-bearing molluscs in the Early Cambrian, diverse shell forms have evolved. Modern molluscs are renowned for a highly complex and robust shell, which is the product of the orchestrated expression of genes and secretion of a large number of proteins and other macromolecules from the epithelium of a specialised organ called the mantle. Molluscan shells display remarkable morphological diversity, structure and ornamentation, however the molecular mechanisms underlying the evolution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 223 publications
0
3
0
Order By: Relevance
“…In mussels Mytilus edulis, chitinrelated enzymes have been shown to play an important role in biochemical defense processes [46]. In a study on mollusk biomineralization, it was reported that there are many tyrosinase genes in the genome of bivalves and qPCR results showed high expression of tyrosinase genes in the mantle tissue of the Pacific oyster C. gigas [47]. In the present study, 15 tyrosinase genes were upregulated during Manila clam D, U, S, J and shell morphology was altered from D to U in Manila clam (Fig.…”
Section: Shell Calcificationmentioning
confidence: 99%
“…In mussels Mytilus edulis, chitinrelated enzymes have been shown to play an important role in biochemical defense processes [46]. In a study on mollusk biomineralization, it was reported that there are many tyrosinase genes in the genome of bivalves and qPCR results showed high expression of tyrosinase genes in the mantle tissue of the Pacific oyster C. gigas [47]. In the present study, 15 tyrosinase genes were upregulated during Manila clam D, U, S, J and shell morphology was altered from D to U in Manila clam (Fig.…”
Section: Shell Calcificationmentioning
confidence: 99%
“…Much of our knowledge on chitin in mollusc shells is thanks to transcriptomic and proteomic approaches. In an attempt to understand the molecular basis underlying shell formation, Aguilera (2014) analyzed the mantle transcriptome of eight bivalve and three gastropod species. This study found over-representation of proteins with polysaccharide-binding domains within the mantle transcriptomes.…”
Section: Chitin and Other Polysaccharidesmentioning
confidence: 99%
“…However, genomic resources will continue to provide profound insight into physiological processes such as biomineralization. There is a growing need for implementation of advanced analytical techniques looking at gene family evolution (Aguilera, 2014;De Bie et al, 2006;Domazet-Lošo et al, 2007) and gene networks (Shannon et al, 2003;Smoot et al, 2011). Further, more "traditional" techniques with a much longer history of use in the field of physiology (see Simkiss Chapter 2 of this volume) should not be forgotten in the "-omics" era.…”
Section: What Does It All Mean?mentioning
confidence: 99%